Embodied Translation, Multimodal, and Situated Communication: An Ethnographic Study of Rink Hockey and Football Multilingual Teams in Macau - Amaro, Vanessa; Jatobá, Júlio (The Journal of Specialised Translation, 2026)
This ethnographic study explores how multilingual athletes in Macau’s rink hockey and football teams translate strategy, affect, and identity across linguistic, bodily, and material boundaries. Drawing on extensive field observation, video analysis, and in-depth interviews, we examine communication through three interconnected lenses: translanguaging (the flexible use of entire semiotic repertoires), intersemiotic translation (converting meaning across speech, gesture, space, and objects), and experiential translation (the affective, embodied negotiation of meaning). On the rink, confined space and fast-paced play generate millisecond cues where verbal and gestural signals converge – Portuguese instructions are echoed in Cantonese and enacted through stick-taps. On the pitch, larger spatial layouts demand role-specific mediators: captains and goalkeepers switch between English, Portuguese, and Chinese codes, while gestures and referee signs help coordinate when words fail. In both sports, hybrid ‘team languages’ emerge, yet linguistic capital remains uneven; Portuguese and English often carry added weight, placing cognitive and emotional burdens on trilingual brokers. Moments of breakdown, such as injury stoppages and tactical disputes, expose how hierarchy, space, and affect decide who is heard and how meaning ultimately reaches others. We demonstrate that sport provides a living laboratory where translation is active: a continuous, multimodal choreography that maintains play while renegotiating notions of power and inclusion.